Influence Of The Phone On The Health Of Tma Students - Yuldasheva F.U; Muzrapova I.A; Toychiboeva D.Sh (Genius Journals, 2025)
Modern technologies have become an integral part of students' lives, but excessive use of mobile phones can have a negative impact on their health. First of all, it leads to deterioration of vision due to constant eye strain and exposure to blue light from the screen. In addition, prolonged use of gadgets in the wrong position contributes to the development of problems with posture and pain in the neck and back. No less important is the impact of smartphones on the psycho-emotional state of students. Constant notifications and active use of social networks can cause anxiety, stress and decreased concentration
Keywords: Computer vision syndrome; postural disorder; insomnia; sleep